Strategi Kebijakan Penerapan Inseminasi Buatan Pada Peternakan Sapi di Provinsi Riau - liza, Yendra; Surnadi; Gazali Lubis, Helmi (IPTEKIN Jurnal Kebijakan Pembangunan dan Inovasi, 2018)
The technology of livestock reproduction begins with the introduction of artificial insemination (IB) technology which aims to make maximum use of a superior male animal. The aim of the study was to asses the knowledge, motivation and adoption of artificial insemination technology by farmers, to find out the socioeconomic characteristics of the breeders and their influence on the level of use and the success rate of the implementation of artificial insemination, and to determine some strategies, policies and application of IB in Riau Province. The method used in this study was survey. Data analysis was SWOT. The study found that motivation, breeders' knowledge in Siak, Indragiri Hulu and Rokan Hulu Regency about artificial insemination technology were high. Adoption of artificial insemination technology in the study location was relatively relatively long adopted by farmers, which was an average of> 60 months. Socio-economic aspects influence the adoption of artificial insemination technology. The strategy that must be created in the implementation of IB in Riau province is an aggressive growth strategy (Growth Oriented Strategy) and competitive advantage.